Strategic Digital Leadership for Business Technology Innovation and Transformation - Maulana, Imam Ryan; Arribathi, Abdul Hamid; Leonie, Natasha (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2026)
Amid rapid technological advancement, organizations are required to undertake digital transformation to remain competitive in the modern business landscape. However, successful transformation requires more than mere technology adoption because it demands strategic leadership capable of driving change, fostering innovation, and aligning organizational objectives with digital strategies. This study examines the role of strategic leadership in organizational digital transformation, highlighting leadership styles, strategic approaches, and key practices that contribute to successful digital change initiatives. Through a comprehensive literature review and case study analysis, the research identifies critical leadership behaviors and decision-making processes that influence the effectiveness of digital initiatives. The findings emphasize that transformational leadership, adaptability, and vision-driven strategies facilitate smoother transitions, enhance employee engagement, and cultivate a sustainable digital culture within organizations. The study also explores major challenges faced by leaders, including resistance to change, resource constraints, and the need to balance innovation with operational stability. The results indicate that strategic leaders who adopt collaborative and inclusive approaches are better positioned to navigate the complexities of digital transformation. By integrating technological capabilities with a clear strategic vision, leaders not only manage transformation processes effectively but also strengthen long-term organizational competitiveness in the evolving digital economy. The study concludes by outlining practical implications for organizational leaders and suggesting directions for future research on the evolving role of leadership in digital transformation.